Ordinances of the Corporation of Georgetown, 1801, October 24th, Sect. 2, The Black Code of the District of Columbia in Force September 1st, 1848, at 50 (1848) - (:unkn) unknown (My University, 1801)
Prohibited "any servant or slave" from shooting any gun or other firearms.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES